Common and uncommon neurological manifestations of neuroborreliosis leading to hospitalization. Issue 1 (December 2017) - Schwenkenbecher, Philipp; Pul, Refik; Wurster, Ulrich; Conzen, Josef; Pars, Kaweh; Hartmann, Hans; Sühs, Kurt-Wolfram; Sedlacek, Ludwig; Stangel, Martin; Trebst, Corinna; Skripuletz, Thomas
Abstract Background Neuroborreliosis represents a relevant infectious disease and can cause a variety of neurological manifestations. Different stages and syndromes are described and atypical symptoms can result in diagnostic delay or misdiagnosis. The aim of this retrospective study was to define the pivotal neurological deficits in patients with neuroborreliosis that were the reason for admission in a hospital. Methods We retrospectively evaluated data of patients with neuroborreliosis. Only patients who fulfilled the diagnostic criteria of an intrathecal antibody production against Borrelia burgdorferi were included in the study. Results Sixty-eight patients were identified with neuroborreliosis. Cranial nerve palsy was the most frequent deficit (50%) which caused admission to a hospital followed by painful radiculitis (25%), encephalitis (12%), myelitis (7%), and meningitis/headache (6%). In patients with a combination of deficits, back pain was the first symptom, followed by headache, and finally by cranial nerve palsy. Indeed, signs of meningitis were often found in patients with neuroborreliosis, but usually did not cause admission to a hospital. Unusual cases included patients with sudden onset paresis that were initially misdiagnosed as stroke and one patient with acute delirium. Cerebrospinal fluid (CSF) analysis revealed typical changes including elevated CSF cell count in all but one patient, a blood-CSF barrier dysfunction (87%), CSF oligoclonal bands (90%), and quantitative intrathecal synthesis of immunoglobulins (IgM in 74%, IgG in 47%, and IgA in 32% patients). Importantly, 6% of patients did not show Borrelia specific antibodies in the blood. Conclusion In conclusion, the majority of patients presented with typical neurological deficits. However, unusual cases such as acute delirium indicate that neuroborreliosis has to be considered in a wide spectrum of neurological diseases. CSF analysis is essential for a reliable diagnosis of neuroborreliosis.